2019
DOI: 10.1089/adt.2019.940
|View full text |Cite
|
Sign up to set email alerts
|

Assays to Interrogate the Ability of Compounds to Inhibit the AF-2 or AF-1 Transactivation Domains of the Androgen Receptor

Abstract: Prostate cancer is the leading cause of cancer and second leading cause of cancer-related death in men in the United States. Twenty percent of patients receiving the standard of care androgen deprivation therapy (ADT) eventually progress to metastatic and incurable castration-resistant prostate cancer (CRPC). Current FDA-approved drugs for CRPC target androgen receptor (AR) binding or androgen production, but only provide a 2-to 5-month survival benefit due to the emergence of resistance. Overexpression of AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Fancher et al, 2019 also report androgen receptor coactivators that have elevated expression in patients with prostate cancer, such as transcriptional intermediary factor 2 (TIF2), steroid receptor coactivator (SRC)-1, RAC3, p300, CBP, Tip60, and ARA70 [ 24 ].…”
Section: Activation Of Androgen Receptor and Cofactorsmentioning
confidence: 99%
“…Fancher et al, 2019 also report androgen receptor coactivators that have elevated expression in patients with prostate cancer, such as transcriptional intermediary factor 2 (TIF2), steroid receptor coactivator (SRC)-1, RAC3, p300, CBP, Tip60, and ARA70 [ 24 ].…”
Section: Activation Of Androgen Receptor and Cofactorsmentioning
confidence: 99%
“…67 Johnston et al have since reported the development of five assays that target the AF-2 domain, although the structures of the hits have not been disclosed to date. 68 More recent work has utilized computational modeling to screen the ZINC database for chemical entities that interact with the AR AF-2. This led to the synthesis of an oxadiazole series of which LHJ-647 was the most potent (Figure 7A).…”
Section: Activation Function 2-targeting Compoundsmentioning
confidence: 99%
“…Of the 286 confirmed active compounds, approximately 60% were able to inhibit or disrupt AR‐TIF2 PPIs with an IC 50 <40 µM 67 . Johnston et al have since reported the development of five assays that target the AF‐2 domain, although the structures of the hits have not been disclosed to date 68 …”
Section: Activation Function 2‐targeting Compoundsmentioning
confidence: 99%